2019
DOI: 10.2478/pomr-2019-0075
|View full text |Cite
|
Sign up to set email alerts
|

Blade Section Profile Array Lifting Surface Design Method for Marine Screw Propeller Blade

Abstract: The lifting surface model is widely used in screw propeller design and analysis applications. It serves as a reliable tool for determination of the propeller blade mean line and pitch distribution. The main idea of this application was to determine the blade shape that would satisfy the kinematic boundary condition on its surface with the prescribed bound circulation distribution over it. In this paper a simplified lifting surface method is presented – in which the 3D task for the entire blade is replaced by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Pitch ratio (P/D) tuning is done by the lifting surface code. The lifting surface model forms a reliable basis for designing blade section profiles and screw propeller blades [16]. As emphasized, thrust, torque, and efficiency results should be the same as the initial conventional propeller.…”
Section: Cavitation Reduction By Cup Methods No Cupped and Cupped Propeller Comparisonmentioning
confidence: 99%
“…Pitch ratio (P/D) tuning is done by the lifting surface code. The lifting surface model forms a reliable basis for designing blade section profiles and screw propeller blades [16]. As emphasized, thrust, torque, and efficiency results should be the same as the initial conventional propeller.…”
Section: Cavitation Reduction By Cup Methods No Cupped and Cupped Propeller Comparisonmentioning
confidence: 99%
“…The lifting surface method for open-water analysis is a classic method similar to that described in [20]. The initial step of the calculations provides a discrete representation of the propeller geometry.…”
Section: Lifting Surface Analysismentioning
confidence: 99%
“…Ships are a contributor to greenhouse gas (GHG) emissions [1], and in recent years, increasing pressure has been placed on the marine industry to decrease GHG emissions through regulatory legislation. IMO (International Maritime Organization) indicated that efficiency improvements could be achieved through operational [2] and technological methods, as these could increase overall performance and decrease fuel consumption [3][4][5][6][7][8][9][10]. Temporary roughness, which refers to temporal changes in the hull and propeller surface roughness, is caused by fouling organisms during a period of service [8].…”
Section: Introductionmentioning
confidence: 99%